2015
DOI: 10.18601/01245996.v17n33.04
|View full text |Cite
|
Sign up to set email alerts
|

Repensar la profundización financiera: estabilidad y crecimiento en los mercados emergentes

Abstract: <p>En este escrito se usa una nueva medida del desarrollo financiero para mostrar que la mayoría de los mercados emergentes aún puede obtener beneficios de crecimiento y estabilidad con un mayor desarrollo financiero. Primero define el desarrollo financiero como una combinación de profundidad, acceso y eficiencia. Luego muestra que el crecimiento económico se debilita a mayores niveles de desarrollo financiero y que el ritmo del desarrollo financiero es importante; además propone una nueva manera de ver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This mechanism works to prevent investors to get excessive return. Sahay et al (2015) also confirmed the above conjecture in their extensive macro cross country study Considering this later view, we find the estimates support our alternative hypotheses. Estimates of INSTITUTION conform a parabolic function: the linear part is positive, while the quadratic part is negative.…”
Section: Baseline Regressionssupporting
confidence: 89%
“…This mechanism works to prevent investors to get excessive return. Sahay et al (2015) also confirmed the above conjecture in their extensive macro cross country study Considering this later view, we find the estimates support our alternative hypotheses. Estimates of INSTITUTION conform a parabolic function: the linear part is positive, while the quadratic part is negative.…”
Section: Baseline Regressionssupporting
confidence: 89%
“…Another macro-categorisation of financial development literature focussed on the determinants of financial development such as the role of institutions such as creditor rights protection (Adeleye et al, 2017;Farla, 2014;Singh, & Huang, 2015), information sharing and financial deepening (Sahay et al, 2015); the role of ICT adoption on financial deepening in Africa (Asongu & Nwachukwu, 2017;Chithralega & Varalakshmi, 2016); outside Africa (Darrat & Al-Sowaldi, 2010;Iscan, 2012;Gadamsetty, 2013;Abosedra & Fakih, 2014;Bansal, 2014;Ho et al, 2017); which all missed out the existence of ICT-innovation interaction and its relationship as a significant macro and micro determinant of financial development. Asongu and Nwachukwu (2017) investigated the role of internet and mobile phone penetration (ICT adoption measures) in complementing financial formalisation and 'in-formalisation' (financial sector development) in improving financial access in Africa using evidence based on generalised method of moments with 53 African countries for the period 2004 À 2011 to establish some findings.…”
Section: Issues In Extant Literaturementioning
confidence: 99%
“…In a later study by (Sahay et al, 2015), it was also found that financial inclusion increases economic development up to a point. Greater access of firms and households to various banking services led to higher growth and that sectors that depend on external finance grow more rapidly in countries with greater financial inclusion.…”
Section: Financial Inclusion and Economic Developmentmentioning
confidence: 90%
“…Financial inclusion, often referred to as the expansion of financial systems, financial services or financial products, so that adults have greater access to society. Statistics have illustrated that many nations have recorded to set financial inclusion implementation as a formal goal to support their economic growth and development (Sahay et al, 2015). It helps in widening the financial network in order to create an effective financial flow within a country's border.…”
Section: Financial Inclusionmentioning
confidence: 99%
See 1 more Smart Citation